Gelatin methacryloyl inverted colloidal crystal scaffolds as artificial liver platform - Shirahama, Hitomi (2018)
Artificial organs are vital for drug development since preclinical animal testing has a limitation in human toxicity prediction, occasionally leading to severe damages. In particular the liver which is an organ that serves the functions in drug metabolism and detoxification, would play a critical role in toxicity screening when reconstructed in vitro. However, primary hepatocytes lose their functions when seeded onto plain substrates, and maintaining the functions ex vivo has been challenging. One of the cues found in liver tissue engineering to keep hepatocyte phenotype is the structural dimensionality; three-dimensional (3D) culture systems which emulate the liver microenvironment, provide enhanced cell-cell interactions and cell-material interactions compared to those in two-dimensions, resulting in prolonged of hepatocyte functions. Therefore, in-vivo-like platforms that mimic the liver microstructure have been in high demand. The overall goal of this dissertation is to create a liver-mimicking platform that can aid in maintaining hepatic functions. Besides cells, the liver is composed of extracellular matrices (ECM) with highly-ordered, porous structure. On the other hand, fabrication of such ECM-based highly-ordered scaffold has been challenging. Problems lie in high viscosity and in slow crosslinking of the aqueous protein solutions for building complex configuration. In this thesis, the material chosen for the platform is a photocrosslinkable protein, gelatin methacryloyl (GelMA). Gelatin is a hydrolyzed form of collagen, which is the main component of the liver structure. While preserving biological advantages of collagen/gelatin, the functionalized gelatin can be crosslinked in minutes in the presence of ultraviolet light and a photoinitiator. Furthermore, aqueous solutions of GelMA are much less viscous than the parent materials. However, the synthesis method has not been optimized in a systematic manner, leaving room for improvement. The first work presented in this thesis is to revamp GelMA synthesis through finding appropriate buffer systems and reaction conditions such as pH, molarity, temperature, and time. The second part of the thesis work entails characterizing the physical properties of GelMA hydrogels with a simplified model. Rheological experiments on mechanical stiffness, swelling measurements in size and mass, and enzymatic degradation experiments were carried out for comprehensive characterization. Finally, a liver-mimicking hydrogel platform was developed, possessing highly-ordered pores and interconnections. Protein-based inverted colloidal crystal (ICC) scaffolds were fabricated with GelMA and a sacrificial polymer lattice. The use of GelMA enabled easy infiltration into the lattices at a high protein concentration and fast crosslinking. Liver model cells, Huh7.5 cells, in GelMA ICC scaffolds attached well to the surface of GelMA ICC and formed 3D cell constructs with cell multi layers during a culture period of high viability. Relative to GelMA plain surface, cells in GelMA ICC exhibited higher hepatic functions. The results demonstrate the potential of GelMA ICC to be an artificial liver platform – that can maintain hepatic functions and foresee human drug toxicity – and would be contributive to drug discovery and development.